2013
DOI: 10.1002/joc.3840
|View full text |Cite
|
Sign up to set email alerts
|

An experiment in intra‐seasonal agricultural drought monitoring and early warning in the Sudano‐Sahelian Belt of Nigeria

Abstract: The highly variable rainfall and recurring drought in dry sub-humid and semi-arid regions constitute a major socio-economic problem that influences people's livelihoods. Agricultural drought is the most common of all drought types and is the most challenging to track and forecast owing to its ease of occurrence and impact on socio-economic sustainability. In Nigeria as is the case in large parts of sub-Saharan Africa, drought frequency, intensity and effect have dominated the literature since the great Sahelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Although crop and livestock production provides employment and are major sources of income for many people in Nigeria, prolonged dry spells have become much more common in recent years, characterized by low crop yields, poor nutrition and death of livestock (Adegboyega et al.,2016). Multi-year droughts are now common which some scientists perceive to be a transitional phase in climate change (Ezeh et al., 2016; Usman and AbdulKadir, 2014). Previous study concluded that annual rainfall has reduced significantly over 20% of the landscape and the amount of annual rainfall reduced by 50–350 mm in 64% portion of Nigeria (Ogungbenro and Morakinyo, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Although crop and livestock production provides employment and are major sources of income for many people in Nigeria, prolonged dry spells have become much more common in recent years, characterized by low crop yields, poor nutrition and death of livestock (Adegboyega et al.,2016). Multi-year droughts are now common which some scientists perceive to be a transitional phase in climate change (Ezeh et al., 2016; Usman and AbdulKadir, 2014). Previous study concluded that annual rainfall has reduced significantly over 20% of the landscape and the amount of annual rainfall reduced by 50–350 mm in 64% portion of Nigeria (Ogungbenro and Morakinyo, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The numerous studies that have been conducted on droughts in Nigeria over the last 40 years have used different indices [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However, without any indication of agricultural drought risk considering varying cropping periods, these studies attempted to characterize droughts generally.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported more erratic behaviour of climate due to climate change, and thus, potentially increase its severity in different countries including Nigeria 9,27,28 . Numerous studies on the variability of climate and the changing nature of droughts using various indices have been conducted in Nigeria 3,[29][30][31][32][33][34][35][36][37][38][39] . Though major drought events have not occurred in Nigeria for the past decades, studies showed an increasing tendency in climate variability, and thus, potential increase in drought frequency and affected areas [40][41][42] .…”
mentioning
confidence: 99%